Distribusi Genotip dan Alel Sifat Kualitatif pada Ayam Silangan - Lubis, Wahyuni; Baharun, Abdullah; Bayu Putra, Widya Pintaka (Seminar Nasional Lahan Suboptimal, 2024)
Lubis, W., Baharun, A., & Putra, W. P. B. (2024). Distribution of genotypes and allales of qualitative traits in cross chicken. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 434-445). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to determine the diversity of phenotypes and genotype distribution of crossbred chickens based on qualitative traits. The crossbred chickens used are crossbred Merawang chickens with other chickens. Merawang chickens are dual-purpose chickens that have great potential to be developed. The main problem with Merawang chickens is that the characteristics of Merawang chickens have not been registered. Efforts made to overcome this problem were by analyzing the genotype distribution of the qualitative traits of Merawang Cross chickens and PCA analysis of the chicken morphostructure. One way to analyze the genotype distribution can be done by calculating the genotype frequency, heterozygosity, and genetic ingression values. This study was conducted using a sample of 26 male and 44 female Merawang Cross chickens. From the entire population of Merawang Cross chickens, the genotype frequency values showed that the dominant phenotype in Merawang Cross chickens was recessive in feather color, feather features, feather shimmer, and comb shape. But it is dominant in shank color which has an allele frequency value of 100% white/yellow. The heterozygosity value shows a medium-value feather color pattern and other phenotypes are low (<30). So, the genotype distribution pattern in Merawang Cross chickens is more dominantly carried by European chickens, the high genetic integration value is found in Rhode Island Red (RIR) chickens reaching 100% in males and 87% in females. This shows that crossbred chickens or Merawang Cross chickens have dominant genes from Rhode Island Red (RIR) chickens.